A case study of the mining exploration in Barangay Paglaum, Tacloban City. - Caliste, Rochelle T. (Rochelle Caliste, 2011)
Brgy. Paglaum is one of the barangays of Tacloban City, Leyte. It was chosen as the research locale of this study.